The Role of Automobiles for the Future of Aluminum Recycling - Modaresi, Roja; Müller, Daniel B (Environmental science & technology, 2012)
To reach required product qualities with lowest costs, aluminum postconsumer scrap is currently recycled using strategies of downgrading and dilution, due to difficulties in refining. These strategies depend on a continuous and fast growth of the bottom reservoir of the aluminum downgrading cascade, which is formed by secondary castings, mainly used in automotive applications. A dynamic material flow model for the global vehicle system was developed to assess the likelihood, timing, and extent of a potential scrap surplus. The results demonstrate that a continuation of the above-mentioned strategies will lead to a nonrecyclable scrap surplus by around 2018 ± 5 if no additional measures are taken. The surplus could grow to reach a level of 0.4–2 kg/cap/yr in 2050, corresponding to a loss of energy saving potential of 43–240 TWh/yr electricity. Various intervention options for avoiding scrap surplus are discussed. Effective strategies need to include an immediate and rapid penetration of dramatically improved scrap sorting technologies for end-of-life vehicles and other aluminum applications.